A short term evaluation of the iodized salt supplementation programme to antenatal mothers in Bachok Kelantan - Ahmad, Zulkifli; Hashim, Noran (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2002)
Iodine is an important micronutrient for physical and mental development. The World Health Organization addressed iodine deficiency disorders as a public health problem as it is endemic in 130 countries all over the world and showed emergence of the condition in some developed country. Malaysia also has some areas endemic for goiter. This study is aitned to detennine the pre\·alence. risk factors~ evaluating the knovvledge. attitude and practices, as well as to assess the effectiveness of the iodized salt supplement in improving iodine status of the antenatal mothers in Bachok. A cross sectional study was conducted at the Health Clinics and Con1munity Clinics in Bachok, Kelantan from 1st July 2001 to 28th February 2002. A self administered pretested questionnaire was used for assessment on the knowledge, attitude and practices of 342 selected antenatal mothers. The effectiveness of the iodized salt supplement was measured with two samples of spot urine for iodine test. The prevalence of iodine deficiency was 63.0 o/o (95% CI: 57.8, 68.2). The first sample mean urinary iodine level was 87.3 (SD 58.64) mcg/1 and the median was 78.0 mcg/1. The total mean score of knowledge, attitude and practices was 58.6 (SD 7 .9), 52.91 (SD) and 42.90 (SD 1 0.9). However, the subjects showed only minimal effort in gaining knowledge and 65% of subjects had never take iodine supplement before. Potential risk factors were analysed by the logistic regression.in which the smoking husband was the risk factor for iodine deficiency with the odd ratio of 2.0. The effectiveness ofthe iodized salt supplementation programme were analysed by the general linear regression analysis. Current iodine level in the blood as well as thelevel of knowledge and correct method of handling the iodized sa1t detennined the in1provement in the iodine status of an individual. In conclusion~ Bachok district can still be considered as area prone for iodine deficiency disorders. The condition could be worsen due. to the poor level of knowledge on the cause~ effect and clinical presentation of the disorders as well as low level of awareness on the disease prevention. However, the iodized salt supplementation programme found was succeed in improving the iodine status among affected antenatal mothers.